Diversidade genética entre cultivares de soja com base em marcadores morfológicos e moleculares - Rodrigues, Lais Nóbrega (2021)
Soybean [Glycine max (L.) Merrill], an annual crop widely produced and consumed around the world, is the main product of the Brazilian agribusiness. In the 2019/2020 crop, Brazil overcome the USA and assumed the position of the world's largest soybean producer. Despite this achievement, it is important that genetic breeding programs continue to develop superior genotypes. In development of new soybean cultivars, the pre-breeding it is essential through studies of genetic diversity. These studies lead to the knowledge of the genetic divergence between possible parents, allowing to obtain wide variability in the segregating generations of future crosses. Therefore, this work aimed to estimate the genetic diversity among 20 soybean cultivars by means genetic distances estimated from 14 morphological descriptors recommended by the UPOV (International Union of New Varieties of Plants) and by the SNPC (Serviço Nacional de Proteção de Cultivares), in different aspects and stages of the plant; and through 39 RAPD markers and 40 microsatellites. Three methods of multivariate analysis were performed: Tocher's optimization and hierarchical (UPGMA) cluster analysis, and the graph (principal coordinates). Overmore, an analysis of the association between the dissimilarity matrices of the morphological and molecular data (RAPD and SSR) was executed. The measures of dissimilarity presented amplitude of 0.075 to 0.85, 0.041 to 0.217 and 0.16 to 0.63 for the morphological descriptors, RAPD markers and microsatellite markers, respectively. The multivariate analyses formed distinct groups, showing that the morphological descriptors, RAPD markers and microsatellite markers used were efficient in distinguishing the 20 soybean cultivars. The correlations between the dissimilarity matrices of the morphological descriptors, RAPD markers and microsatellite markers were low (0.26371, 0.1192 and 0.188989, respectively), indicating that the morphological descriptors, RAPD markers and microsatellites complement each other in distinguishing the 20 cultivars. Was concluded that have a genetic variability among the 20 cultivars studied for the morphological descriptors, RAPD markers and microsatellites used. In addition, it is clear that in the study of genetic diversity, molecular markers can be used as a way of complementing the morphological descriptors.